What to expect when China liberalizes its capital account - Mark Kruger; Gurnain Kaur Pasricha (Bank of Canada, 2016)
When China joined the World Trade Organization in December 2001, it marked a watershed for the world economy. Ten years from now, the opening of China's capital account and the financial integration that will unfold will be viewed as a milestone of similar importance. This paper discusses the benefits, to China and the rest of the world, of deepening China's capital account liberalization. We assess China's current level of de jure and de facto integration, in relation to other G20 economies. We update the Pasricha et al. (2015) data on capital control actions to 2015 for China, to assess China's international financial integration. We also look at its relative international investment position to gauge its de facto integration. We then estimate the size and composition of capital flows likely to ensue assuming that China's further capital account liberalization results in its gross international investment position converging to that of the G20 average. In addition, we discuss the risks involved with the further opening of China's capital account and how they can best be managed. We also emphasize the potentially stabilizing effects of residents' flows and the importance of liberalizing inflows and outflows in a balanced way and at the same time.
Keywords: F31; F32; G18; 330; International topics; Exchange rate regimes; Balance of payments and components